Occurrence of Os Rostrale in a Buffalo (Bubalus bubalis) Skull - B.V., Prakruthi.; H.S., Patki; K.P., Surjith.; C.V., Rajani.; V.R., Indu.; S., Maya.; Abraham., John; P.S., Navya. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The Os rostrale, also known as the prenasal bone, is commonly found in members of the Suidae family, particularly in pigs. It completes the snout's rigid skeleton, aids in digging and provides structural integrity during excavation activities. However, its occurrence in bovines, including buffalo breeds, is rare and understudied. This study aimed to explore the morphological and histological features of the Os rostrale in an adult Pandharpuri buffalo. Additionally, it aimed to investigate the rarity of the occurrence of Os rostrale in buffalo skulls. After careful gross morphological observations, the Os rostrale of an adult Pandharpuri buffalo was subjected to radiographic analysis and histological examination. The Os rostrale appeared sword-shaped with a mediolateral curvature and was radio-opaque. Histological analysis revealed active hyaline cartilage transitioning into compact bone with Haversian system, indicating its endochondral ossification. Despite belonging to an adult animal, the structure retained cartilage elements, suggesting a slow replacement process requiring further investigation. This study provided essential baseline information regarding the Os rostrale in buffaloes, contributing to a better understanding of its structural significance. Additionally, it sheds light on the unusual occurrence of the Os rostrale in buffalo skulls, which is uncommon within the Bovidae family.